2007
DOI: 10.1091/mbc.e06-11-1054
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Underlying the Iron-dependent Nuclear Export of the Iron-responsive Transcription Factor Aft1p inSaccharomyces cerevisiae

Abstract: Aft1p is an iron-responsive transcriptional activator that plays a central role in maintaining iron homeostasis in Saccharomyces cerevisiae. Aft1p is regulated primarily by iron-induced shuttling of the protein between the nucleus and cytoplasm, but its nuclear import is not regulated by iron. Here, we have shown that the nuclear export of Aft1p is promoted in the presence of iron and that Msn5p is the nuclear export receptor (exportin) for Aft1p. Msn5p recognizes Aft1p in the iron-replete condition. Phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
92
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 52 publications
(76 reference statements)
2
92
0
1
Order By: Relevance
“…This agrees with a recent study showing that the iron-dependent dissociation of Aft1 from the promoter is the critical step in the regulation of iron metabolism (Ueta et al 2012). Thus, unlike what was previously suggested (Yamaguchi-Iwai et al 2002;Ueta et al 2003Ueta et al , 2007, the way Aft1 regulates iron homeostasis depends more on its capacity to bind its target DNA sequence than on its capacity to shift from the cytosol to the nucleus. Comparative sequence analysis of the DNA-binding domains of various Aft proteins showed that Aft1(152-203), which we named "VS", is a rapidly evolving sequence, bordered by two conserved regions designated CS1 and CS2.…”
Section: Discussionsupporting
confidence: 91%
“…This agrees with a recent study showing that the iron-dependent dissociation of Aft1 from the promoter is the critical step in the regulation of iron metabolism (Ueta et al 2012). Thus, unlike what was previously suggested (Yamaguchi-Iwai et al 2002;Ueta et al 2003Ueta et al , 2007, the way Aft1 regulates iron homeostasis depends more on its capacity to bind its target DNA sequence than on its capacity to shift from the cytosol to the nucleus. Comparative sequence analysis of the DNA-binding domains of various Aft proteins showed that Aft1(152-203), which we named "VS", is a rapidly evolving sequence, bordered by two conserved regions designated CS1 and CS2.…”
Section: Discussionsupporting
confidence: 91%
“…These results also lead to the question of how [2Fe-2S] Fra2-Grx3/4 influences the transcriptional activity of Aft1/2. As mentioned earlier, the FraGrx signaling pathway is proposed to induce oligomerization of Aft1 (and presumably Aft2) under iron-replete conditions (5,33). This conformational change, in turn, may promote export of Aft1/2 from the nucleus or prevent interaction of Aft1/2 with the target DNA.…”
Section: Discussionmentioning
confidence: 89%
“…It has been suggested previously that Msn5 specifically exports phosphoproteins because several Msn5 cargoes, such as Pho4, Mig1, Crz1, Aft1, Cdh1, and HO, have to be phosphorylated to be relocated out of the nucleus (17)(18)(19)(20)(21)(22)(23). However, binding of Msn5 to other cargoes, such as Far1, does not depend on the cargo phosphorylation state (24).…”
Section: Discussionmentioning
confidence: 99%